2017
DOI: 10.1038/srep40852
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Phosphoproteomics Reveals an Important Role of MKK2 in Banana (Musa spp.) Cold Signal Network

Abstract: Low temperature is one of the key environmental stresses, which greatly affects global banana production. However, little is known about the global phosphoproteomes in Musa spp. and their regulatory roles in response to cold stress. In this study, we conducted a comparative phosphoproteomic profiling of cold-sensitive Cavendish Banana and relatively cold tolerant Dajiao under cold stress. Phosphopeptide abundances of five phosphoproteins involved in MKK2 interaction network, including MKK2, HY5, CaSR, STN7 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 70 publications
2
37
0
Order By: Relevance
“…The aquaporin results in this study support the observed phenotype that the leaves of Cavendish quickly wilted but no difference was observed in Dajiao under cold treatment. Meanwhile, we found that there was no difference in stomatal conductance and transpiration rate between Cavendish and Dajiao ( Gao et al, 2017 ). Since water status of plant leaves is dependent on both stomatal regulation and water supply from the vasculature to inner tissues, water appears to be supplied more effectively from the vasculature in Dajiao than in Cavendish.…”
Section: Discussionmentioning
confidence: 88%
“…The aquaporin results in this study support the observed phenotype that the leaves of Cavendish quickly wilted but no difference was observed in Dajiao under cold treatment. Meanwhile, we found that there was no difference in stomatal conductance and transpiration rate between Cavendish and Dajiao ( Gao et al, 2017 ). Since water status of plant leaves is dependent on both stomatal regulation and water supply from the vasculature to inner tissues, water appears to be supplied more effectively from the vasculature in Dajiao than in Cavendish.…”
Section: Discussionmentioning
confidence: 88%
“…Physiological and proteomic responses to cold stress are observed in banana [ 35 37 ]. Clarifying the cold-induced genome-wide gene expression patterns and changes in lncRNAs levels via high throughout RNA-sequencing is needed for elucidating the regulatory pathways mediating cold responses in wild banana.…”
Section: Introductionmentioning
confidence: 99%
“…The protein isolation and Western blot analysis of banana ECSs were performed as previously (Gao et al, 2017). Briefly, total proteins of Cavendish banana ECS lysates were prepared in icecold phosphate-buffered saline (PBS) (100 mM, pH 7.5) containing 1 mM EDTA, 100 lg ml À1 PMSF, 0.1% Triton X-100 and protease/phosphatase inhibitor cocktails (Roche).…”
Section: Protein Extraction and Western Blottingmentioning
confidence: 99%